2021
DOI: 10.1039/d0fo03379k
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of rejected unripe plantain fruits ofMusaAAB Simmonds: from nutritional characterisation to the conceptual process design for prebiotic production

Abstract: The increasing consumption of plantain fruits with specific quality standards generates high agricultural waste. This work aimed at valorising the rejected unripe pulp of Dominico-Hartón plantain fruits (Musa AAB Simmonds)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
6
1
1
Order By: Relevance
“…During the second stage, mass loss occurs at 220-361 °C, showing maximum mass loss (52.09%) and minimum derivative value. Tese showed that the depolymerization of the carbohydrate chain results in the decomposition of amylose and amylopectin and released gaseous compounds [32,51]. Te present mass loss value was lower than the value reported for the rejected plantain fruit, which was 10.79 ± 0.04 and 59.3 ± 0.1% for frst-and second-stage mass loss [51].…”
Section: Termalcontrasting
confidence: 54%
See 2 more Smart Citations
“…During the second stage, mass loss occurs at 220-361 °C, showing maximum mass loss (52.09%) and minimum derivative value. Tese showed that the depolymerization of the carbohydrate chain results in the decomposition of amylose and amylopectin and released gaseous compounds [32,51]. Te present mass loss value was lower than the value reported for the rejected plantain fruit, which was 10.79 ± 0.04 and 59.3 ± 0.1% for frst-and second-stage mass loss [51].…”
Section: Termalcontrasting
confidence: 54%
“…Tese showed that the depolymerization of the carbohydrate chain results in the decomposition of amylose and amylopectin and released gaseous compounds [32,51]. Te present mass loss value was lower than the value reported for the rejected plantain fruit, which was 10.79 ± 0.04 and 59.3 ± 0.1% for frst-and second-stage mass loss [51]. Similarly, Cordoba et al [32] reported a higher mass loss of green bananas in the frst (12.65 °C) and second stage of decomposition (66.69-68.88 °C).…”
Section: Termalmentioning
confidence: 99%
See 1 more Smart Citation
“…La conversión física puede aplicarse al aprovechamiento del pseudotallo de plátano para la extracción de fibras (Cadena et al, 2017;Gañán et al, 2008) y para obtener alimentos para animales (producción de bloques nutricionales y ensilaje) (Díaz et al, 2013;Gómez, Sánchez, Teixeira, et al, 2020;Suárez et al, 2018). Por otra parte, la conversión biológica es una alternativa para obtener productos como jarabes de fructosa y glucosa (Gómez, Sánchez, & Correa, 2020;Hernández et al, 2008) y compuestos prebióticos como los derivados de la maltosa (Chockchaisawasdee & Poosaran, 2012;Gómez et al, 2021) y azúcares fermentables para la obtención de bioetanol (Souza et al, 2014) y biogás.…”
Section: Discussionunclassified
“…Pasting measurements were performed in an HR-1 rheometer (TA Instruments, New Castle, DE, USA) equipped with a Peltier plate (40 mm, 1000 µm gap) as described by Gómez et al [ 36 ]. Five grams of chestnut starch in 100 mL of distilled water with 24 h of hydration were used in the analysis.…”
Section: Methodsmentioning
confidence: 99%